Pengetahuan dan Sikap Keluarga terhadap Pencegahan Penyakit Tuberculosis di Wilayah Kerja Puskesmas Wundulako Tahun 2026 - Elma Elmika; Nurwahyuni Nurwahyuni; Nur Afni (Yayasan Literasi Sains Indonesia, 2026)
Background: Tuberculosis (TB) remains a major public health problem and one of the leading infectious diseases worldwide. The success of TB transmission prevention is strongly influenced by family knowledge and attitudes toward disease prevention efforts. Objective: This study aimed to determine the relationship between family knowledge and attitudes toward the prevention of tuberculosis transmission in the working area of Wundulako Public Health Center. Methods: This study employed a quantitative cross-sectional design involving 39 respondents selected according to the study criteria. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses. The relationship between variables was tested using the Spearman Rank test with a significance level of 0.05. Results: The majority of respondents were aged 26–35 years (53.9%), female (87.2%), had a senior high school education (64.1%), and were categorized in other occupations (74.3%). Most respondents demonstrated good knowledge regarding TB (76.9%), while 92.3% showed positive attitudes toward TB prevention. Bivariate analysis revealed a significant relationship between family knowledge and attitudes and the prevention of TB transmission, with a p-value of 0.001 (p<0.05). Conclusion: Good knowledge and positive family attitudes are significantly associated with efforts to prevent TB transmission. Strengthening health education programs and enhancing family involvement are essential strategies to support tuberculosis control and prevention within the community.